COVID-19 vaccination, political partisanship, and moral values - Piergiuseppe Fortunato; Alessio Lombini (University of Neuchâtel, Institute of Economic Research (IRENE), 2022)
This paper examines the association between political partisanship and willingness to vaccinate against COVID-19 in the US. It shows that those counties with a stronger lead of the Republican candidate during the latest presidential electoral rounds displayed consistently lower vaccination rates (1st and 2nd dose) than swing counties and Democratic strongholds. The paper also examines how partisanship interacts with socio-demographic variables such as education, income per capita, and ethnic composition in affecting vaccination attitudes. The results remain qualitatively unaffected when taking into consideration differences in the timing and intensity of vaccination campaigns across states and the potential endogeneity of political preferences. Our results also highlight how the specific combination of moral values that characterize the Republican electorate might explain the observed association between partisanship and vaccination rates.
Keywords: I12; I18; Z13; 330; COVID-19; Vaccination; Partisanship; Moral Values